Patient-Reported Anxiety/Depression After Endovascular Thrombectomy: A post-hoc Analysis of Direct-MT Trial - Zhang, Ping; Shen, Hong-jian; Chen, Lei; Zhu, Xuan; Zhang, Min-min; Jiang, Yi; Yang, Peng-fei; Zhang, Lei; Xing, Peng-fei; Ye, Xiao-fei; Lou, Min; Yin, Cong-guo; et al. (Frontiers in Neurology, 2022)
Objective To analyze the effect of endovascular thrombectomy (EVT) alone vs. EVT after an intravenous (IV) alteplase of ischemic stroke on a patient-reported anxiety/depression, and to identify predictors of patient-reported anxiety/depression by analyzing data from Direct Intraarterial Thrombectomy in Order to Revascularize the patients with Acute Ischemic Stroke with a Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals: a Multicenter Randomized Clinical Trial (DIRECT-MT). Methods Patients with acute ischemic stroke (AIS), triggered by a large-vessel occlusion in the anterior circulation, were randomly allocated to undergo an EVT after IV alteplase (combination-therapy group) or an EVT alone (EVT-alone group) at a 1:1 ratio in DIRECT-MT. Patients in both groups were followed up for 90 days (±14 days) after stroke using a structured modified Ranking Scale (mRS), a Barthel Index (BI), and a 5-Dimensional European Quality of Life Scale (EQ-5D-5L). Patients who returned EQ-5D-5L were included. The EQ-5D-5L anxiety/depression dimension was used to analyze the patient-reported anxiety/depression. First, differences in patient-reported anxiety/depression were compared between the combination-therapy group and the EVT-alone group. Then, the baseline and influencing factors between the anxiety/depression group and no anxiety/depression group were analyzed using univariate regression analysis. Finally, variables with p < 0.1 in univariate regression were subjected to multivariable binary regression analysis to screen independent predictors for patient-reported anxiety /depression after ischemic stroke. Results : Five hundred fifteen patients returned the EQ-5D-5L in Direct-MT. Of these patients, 226 (43.88%) reported a level of anxiety/depression, and about 7% reported a severe or extremely severe anxiety/depression. The patient-reported anxiety/depression in the EVT-alone group was significantly higher than that in the combination-therapy group (48.26% vs. 39.45%, p = 0.04). The clinical outcomes were significantly different between the no Anxiety/Depression Group and the anxiety/depression group (mRS at 90 days:2 vs 3, p < 0.001; BI of 95 or 100 at 90 days: 73.36% vs 42.04%, p < 0.001; EQ-5D-5l utility indexes at 90 days:0.96 vs.57, p < 0.001). Logistic regression analysis showed that allocation to thrombolysis before EVT strategy was inversely associated with anxiety/depression [0.61(0.40, 0.94), p = 0.03], an insular cortex ischemia, and National Institute of Health Strocke Scale (NIHSS) at 7 days were positively associated with anxiety/depression [2.04(1.07, 3.90), p = 0.03; 1.07(1.03, 1.12), p < 0.001]. Conclusions Patient-reported anxiety/depression may suggest that there is a benefit to administering intravenous alteplase before EVT. It may also indicate that it is better to provide IV alteplase before EVT, rather than EVT alone according to patient-reported anxiety/depression. Future research should consider not only the motor function impairments but also the patient-reported mental problems as measures of treatment efficacy in patients with stroke (DIRECT-MT ClinicalTrials.gov number, NCT03469206).